Artificial intelligence in operational applications of railway infrastructure manager - Přemysl Šrámek; Jaromír Široký; Martin Vojtek (Acta Polytechnica CTU Proceedings)
The main goal of this article is to present the possibility of using artificial intelligence in operational application of railway infrastructure manager. Railway 4.0 can be controlled fully digitally – operational applications based on the artificial intelligence can optimize the technology of railway traffic control. Thereafter, a wide range of equipment could be controlled by application through a secure interface.